(untitled) (Journal of Shaheed Suhrawardy Medical College, 2020)
Objectives: To determine the pregnancy outcome among anemic women admitted in labour ward of a tertiary level hospital. Methodology: This is a descriptive type of cross-sectional study. All women who were admitted at labour room for delivery with anemia and gestational age more than 28 weeks were included with purposive sampling under the GU-3 of Shaheed Suhrawardy Medical College & Hospital. Respondents were recruited on the basis of clinical findings correlating with lab investigation. Blood samples were collected during the time of admission and hemoglobin (Hb) level were tested by automated machine in the laboratory of ShSMCH. Outcome of pregnancy was observed against the anemic state defined by Hb% done in laboratory. The mother who delivered, intra-partum & post-partum observation up to 7 days were made for pregnancy outcome.Results: This study conducted in a tertiary level public hospital, included 100 pregnant anemic mothers admitted at labor ward. Prevalence of anemia was 30.12% among the pregnant women at delivery. It revealed that women went into labor having mild anemia in 77% and moderate anemia in 23% cases. Importantly it was observed that moderate anemia was found more in younger age group. Additionally, it was also more pronounced (>50%) among the illiterate and primary education group. There was significant inverse relationship between educational status (p =.003) and anemia. Regarding family history, about two thirds anemic mother came from nuclear family and they also lives with small members. Most of the multigravida women presented with moderate anemia. Among the moderately anemic mothers’ interval of pregnancy were less than two years. It has been observed that 60.9% moderate anemic mother was not on regular antenatal checkup and total 11% respondents had no antenatal checkup. Regarding maternal outcome preterm labour (PTL), premature rupture of membrane (PROM), wound infection were more among moderately anemic group. There was significant relationship between degree of anemia with birth weight (p=.014). Adverse fetal outcome like prematurity, NICU admission, IUD were found more among moderately anemic mothers. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 155-160